Communication and Advertising: Historical Development, Challenges, and Prospects - Jagadish, Ravi (Journal of Global Economy, Business and Finance, 2025)
India's advertising landscape has undergone a significant transformation, evolving from traditional print and broadcast media to a dynamic digital ecosystem. Communication strategies have shifted alongside cultural, economic, and technological changes, presenting both opportunities and challenges for advertisers. This paper explores the evolution of communication and advertising in India, examining the influence of regional diversity, digital proliferation, consumer behavior, and government regulations. The study also delves into the role of social media, influencer marketing, and programmatic advertising, highlighting the growing importance of personalized and culturally nuanced campaigns. The paper concludes with a discussion on the future of advertising in India, focusing on sustainability, ethical practices, and the integration of emerging technologies.